Systematic analysis of lysine malonylation in Streptococcus mutans - Li, Zhengyi; Wu, Qinrui; Zhang, Yixin; Zhou, Xuedong; Peng, Xian (Frontiers in Cellular and Infection Microbiology, 2022)
Protein lysine malonylation (Kmal) is a novel post-translational modification (PTM), which is involved in regulating various biological pathways, such as energy metabolism and translation. Malonylation in prokaryotes, however, are still poorly understood. In this study, we performed a global Kmal analysis in the cariogenic organism Streptococcus mutans using the combination of antibody-based affinity enrichment and high-resolution LC-MS/MS analysis. Altogether, 392 malonyllysine sites in 159 proteins were identified. Subsequent bioinformatic analysis revealed that Kmal occurs on the proteins involved in a variety of metabolic pathways including translation machinery, energy metabolism, RNA degradation and biosynthesis of various secondary metabolites. Quantitative analysis demonstrated that Kmal substrates were globally altered in the biofilm growth state compared with that of planktonic growth. Furthermore, comparative analysis of lysine malonylome of our study with previously determined lysine acetylome in S. mutans showed that a small proportion of Kmal sites was overlapped with acetylated sites, suggesting that these two acylations have distinct functional implications. These results expand our knowledge on Kmal in prokaryotes, providing a resource for researching metabolic regulation of bacterial virulence and physiological functions by PTM.